Debt Capital and Dividend Policy as Complementary Indicators of Firm Valuation - Okechukwu Enyeribe Njoku; Younghwan Lee (International Journal of Financial Studies)
This study investigates the interdependencies between debt capital and dividend policy as complementary factors influencing firm value among corporations listed on the Korea Composite Stock Price Index (KOSPI). Using Tobin’s Q as a firm value metric and employing robust econometric techniques (OLS, 2-SLS, and GMM), the analysis reveals that while debt and dividend policies independently reduce firm value, their interaction produces a synergistic effect that increases value. The findings further indicate the dual role of Chaebol ownership structures, which, despite their association with lower firm value, mitigate the negative effects of financial policies. Additionally, firm size is found to negatively impact value, whereas free cash flow has a significant positive effect. By disentangling the complex dynamics of capital structure, dividend strategies, and ownership configurations, this study offers actionable insights for managers, investors, and policymakers. It emphasizes the importance of balanced financial practices and governance reforms tailored to concentrated ownership environments.